Penerapan Model PjBL melalui Pendekatan CRT untuk Meningkatkan Hasil Belajar Matematika Kelas 1 SDN Putat Jaya IV-380 Surabaya - Fadilah Ilmi Auliya; Desi Eka Pratiwi; Herlia Nimas Ayu Hastungkoro (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
The lack of student interest and motivation which has an impact on low mathematics learning outcomes is the background of this class action research. This study aims to improve the learning outcomes of grade I students on flat building materials through the application of the Project-Based Learning (PjBL) model with the Culturally Responsive Teaching (CRT) approach. The research method used is Classroom Action Research (PTK) model Kemmis and Mc. Taggart model with two cycles, each of which consists of planning, implementation, observation, and reflection stages. The results showed that the application of the PjBL model through the CRT approach can improve student learning outcomes. This was shown by an increase in the percentage of classical learning completeness from 44.44% in cycle I to 88.88% in cycle II, as well as an increase in the average N-Gain from 0.35 (medium category) in cycle I to 0.66 (medium category) in cycle II. Thus, the PjBL model with the CRT approach can effectively be used in learning mathematics to improve student learning outcomes.